Evaluation of the right parasternal four-chamber view for the assessment of left ventricular longitudinal strain and strain rate by two-dimensional speckle tracking echocardiography in dogs. (October 2018) - Santarelli, Giorgia; Talavera López, Jesús; Fernández del Palacio, Josefa
Abstract: Two-dimensional (2-D) speckle tracking echocardiography (STE) is a relatively new imaging technique, introduced in veterinary medicine to aid the assessment of left ventricular (LV) myocardial function. Among other indices, LV longitudinal strain and strain rate (SR) can be measured with this modality, and in dogs they are usually obtained from the left apical four-chamber (LAp4Ch) view. However, in this species, a good quality right parasternal four-chamber (RP4Ch) view can generally be attained, and the aim of this study was therefore to determine its feasibility and reliability for longitudinal strain and SR assessment, and to establish whether the two projections can be used interchangeably. Fifty-one healthy dogs and twenty-five dogs with various cardiac diseases were examined. Longitudinal global and segmental strains and global SR of the LV were obtained with 2-D STE by use of RP4Ch and LAp4Ch views. Intra-observer (within-day and between-day) and inter-observer variabilities were established, and strain and SR values obtained from the two views were compared. The RP4Ch view demonstrated to be feasible for the assessment of longitudinal strain and SR by use of 2-D STE in healthy and diseased dogs. However, out of sector motion of the apical segments could occur and induce tracking errors. The deformation parameters obtained from this view and the LAp4Ch view were often significantly different, and therefore they should not be used interchangeably. Further, the software employed in the present study performed better global than segmental strain analysis for both views. Highlights: The right parasternal four-chamber view is used for longitudinal strain analysis. The analysis from this view demonstrated to be feasible and reliable in dogs. It should not be used interchangeably with the left apical four-chamber view.